2019
DOI: 10.1038/s41598-019-45369-8
|View full text |Cite
|
Sign up to set email alerts
|

Statins exacerbate glucose intolerance and hyperglycemia in a high sucrose fed rodent model

Abstract: Statins are first-line therapy drugs for cholesterol lowering. While they are highly effective at lowering cholesterol, they have propensity to induce hyperglycemia in patients. Only limited studies have been reported which studied the impact of statins on (a) whether they can worsen glucose tolerance in a high sucrose fed animal model and (b) if so, what could be the molecular mechanism. We designed studies using high sucrose fed animals to explore the above questions. The high sucrose fed animals were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…However, when a longer duration of simvastatin treatment (i.e up to 80 days) was applied, significant weight loss was observed. (4) The main finding of the present study (Figure 1) revealed a significantly lower level of skeletal muscle PGC-1α in the simvastatin group compared to the control group (p = .026). This is similar to the study by Goodman et al(2015) which found a decrease in PGC-1α levels in the soleus muscles of mice given simvastatin 60 mg kg -1 day -1 and simvastatin 80 mg kg -1 day -1 for 2 weeks.…”
Section: Resultssupporting
confidence: 52%
“…However, when a longer duration of simvastatin treatment (i.e up to 80 days) was applied, significant weight loss was observed. (4) The main finding of the present study (Figure 1) revealed a significantly lower level of skeletal muscle PGC-1α in the simvastatin group compared to the control group (p = .026). This is similar to the study by Goodman et al(2015) which found a decrease in PGC-1α levels in the soleus muscles of mice given simvastatin 60 mg kg -1 day -1 and simvastatin 80 mg kg -1 day -1 for 2 weeks.…”
Section: Resultssupporting
confidence: 52%
“…We found no overlap in statistically significant endpoints for DEA and statins except for decreased LDL/HDL ratios for DEA (9.8%; our 3-week study) versus statins [26.7%; 18-24month study (64)]. However, statins may increase hyperglycemia and risk for T2D (65) especially on a high carbohydrate diet (66) and their adverse effects include severe muscle condition; rhabdomyolysis, further exacerbated by metabolic syndrome (67). Thus, the population that cannot tolerate statins may benefit from DEA treatment that may lower the risk of progressive diseases initiated and driven by dyslipidemia.…”
Section: Discussionmentioning
confidence: 62%
“…Patients not treated with statins were more likely to improve HbA1c levels after transitioning to therapy with insulin pump. While several studies have shown an association of treatment with statins and increased HbA1c levels and risk of diabetes in the general population and in type 2 diabetes, [34][35][36] few studies assessed this association in T1D. In the Thousand & 1 Study, use of statins was independently associated with increased HbA1c in patients T1D.…”
Section: Discussionmentioning
confidence: 99%